Some Plants Used for Reproductive Health by Women in Agbarha-Otor Community, Delta State - Mark Aihiokhai; MacDonald Idu; Thessy Arueyingho (International Journal of Applied Biology, 2022)
Overtime, the state of maternal health in Nigeria is poor and can be attributed to inadequate access to reproductive health services, poverty and in some areas, cultural resistance. Medicinal plants used in Agbarha-Otor, Ughelli, Nigeria for managing women’s reproductive health during pregnancy, birth and post-partum were investigated in this study. Surveys were conducted using semi structured questionnaire as well as guided field-walks where respondents, specifically, Traditional Birth Attendants (TBAs), were interviewed. A total of 30 plants belonging to 23 families having properties against different conditions, ailments and peculiarities relating to gynaecological conditions in women were documented. Most of the documented plants belong to Asteraceae family. Also, most of the reported plants were majorly herbs and shrubs which were surveyed plants from the wild. Leaves were the most frequently used plants’ part. Most of the medications were prepared as decoctions and mostly administered orally. From the survey, it can be deduced that the use medicinal plants for reproductive healthcare and gynaecological conditions in the study area is still in practice. Scientific validation of the biological properties of the surveyed plants is highly advocated and cultivation of medicinal plants to minimize the pressure on wild species is also recommended.